CLINICO MYCOLOGICAL PATTERN OF FUNGAL RHINOSINUSITIS - A STUDY FROM A TERTIARY CARE CENTRE - ANANDHILAKSHMANAN,; ANANDHALAKSHMI.S,; SELVARAJAN G, (International Journal of Pharma and Bio Sciences, 2014)
Nose and Paranasal sinuses are being constantly exposed to the environment.Hence fungus are increasingly being implicated in the etiology of rhinosinusitis. It is a cause of morbidity and mortality, especially when it is invasive fungal sinusitis.To study the fungal profile of sinusitis in a tertiary care centre in South India and correlate with clinical findings and histopathology. Classification into clinical types was also attempted. Samples were received from suspected cases of fungal sinusitis, confirmed by radiography (heterogenous opacity with sinus expansion CT scan) from the Department of Otorhinolaryngology, SRM Medical College and Hospital. The endoscopic aspirates of tissue samples were examined microscopically and subjected to culture. Species identification was done by standard microbiological methods. Histopathological (HPE) findings were also correlated. A total of 84 patients were enrolled in the study, which included 50 (60%) males and 34 (40%) females. The maximum number of specimen (44) received were in the age group of 21-40 years. Among the 84 specimens, 54 were culture positive. Aspergillus spp (40%) was reported to be the major isolate,Aspergillusflavus being (63%), followed by Aspergillus fumigates (29%). Allergic Fungal RhinoSinusitis (AFRS) was the most common clinical type (66%) and in the majority of these cases the causative agent was Aspergillusflavus.Fungal infections of the paranasal sinuses are not uncommon, especially in tropical region, hence it is important to identify early and treat patients timely to prevent complications.